Functional polymorphism among members of abscisic acid receptor family (ZmPYL) in maize - Feng-zhong LU; Hao-qiang YU; Si LI; Wan-chen LI; Zhi-yong ZHANG; Feng-ling FU (Journal of Integrative Agriculture, 2020)
Pyrabactin resistance 1-like proteins (PYLs) are direct receptors of abscisic acid (ABA). For the redundant and polymorphic functions, some members of the PYL family interact with components of other signaling pathways. Here, 253 positive colonies from a maize cDNA library were screened as interacting proteins with the members of ZmPYL family. After sequencing and function annotation, 17 of 28 interaction combinations were verified by yeast two-hybrid (Y2H). The germination potential, taproot length and proline content of a quartet mutant of Arabidopsis PYL genes were significantly deceased comparing to the wild type (WT) under alkaline stress (pH 8.5) and 100 µmol L−1 methyl jasmonate (MeJA) induction. The malondialdehyde (MDA) content was significantly increased. After germinating in darkness, the characteristics of dark morphogenesis of the quartet mutant seedlings were more obvious than those of the WT. The differential expression of the related genes of photomorphogenesis in the mutant was much more than that in the WT. Three light and two JA responsive cis-affecting elements were identified during the promoter sequences of the AtPYL1 and AtPYL2 genes. These results suggested that functional polymorphism has evolved among the members of ZmPYL family. In response to developmental and environmental stimuli, they not only function as direct ABA receptors but also interact with components of other signaling pathways mediated JA, brassinosteroid (BR), auxin, etc., and even directly regulate downstream stress-related proteins. These signaling pathways can interact at various crosstalk points and different levels of gene expression within a sophisticated network.